Review Article: Effect Anticancer Drug of Histological Alteration and Improvement their Effects by Natural Antioxidants - Salman, Raghad Jawad; Shoker, Roaa M. H.; Jebur, Hakim Bahlok (Journal for Research in Applied Sciences and Biotechnology, 2023)
Usually, Cancer and anticancer drugs can produce harmful side effects, side effects which occur in tissues or organs and produce adverse histopathological change. Cancer treatment by radiotherapy and chemotherapy, and chemotherapy treatments is more mostly used all over the world. Generally, chemotherapy drugs cusses the damage by free radicals and produce cytotoxicity. Natural antioxidant compounds of daily diet are more effective to scavenge or neutralize the free radicals which create by chemotherapy drugs and finally, improvement histopathological change.